Pendampingan UMKM dalam Penggunaan Digital Marketing pada UMKM Barokah - Ita Purnama; Fanisyah Aulia Putri; Kurnia Fajrianti (Lembaga Pengembangan Kinerja Dosen, 2025)
The purpose of this community service is to develop MSMEs in terms of digital marketing and also expand the MSME marketing network. MSME Barokah is one example of MSMEs that need digital marketing assistance. The methods used in community service activities are divided into four stages, namely, surveys, digital marketing socialization, digital marketing assistance, and maintenance and evaluation stages. The form of community service is aimed at developing and also in digital marketing assistance for MSME Barokah so that they can have an unlimited marketing network